Chronic Disease Management Programs Based On Caring Theory With Blood Pressure Reduction - Hastuti, Apriyani Puji; Kurniawan, Ardhiles Wahyu; Mufarokhah, Hanim (Universitas STRADA Indonesia, 2021)
Background: Hypertension cases to overcome the patient's hypertension condition would be well or prosperous condition and the patient could prevent complications and control blood pressure. Activities in Chronic Disease Management Program (Prolanis) include medical or educational consultations, home visits, reminders, club activities.Purpose: This study aimed to analyze the application of the prolanis program based on the caring theory by reducing blood pressure in hypertensive patients.Methods: The design of this research is pre-experimental with cross sectional study approach. The population in this study were all patients with hypertension who took part in management program activities in the public health center (PHC), a number of 40 people, with the sampling technique used was accidental sampling and the total sample was 28 people. The data collection method used a questionnaire. The data analysis of this research is to use the Paired t test.Results: The result of this study is that there is a relationship between the application of a chronis disease management programs based on caring theory with blood pressure reduction with an average systolic blood pressure before the intervention of 142?26.15 and after the intervention of 138?1.21 with p= 0.000 which means that the module intervention can decrease systolic and diastolic blood pressure. While for diastolic blood pressure, the results of the study showed that the mean blood pressure before the intervention was 85?10.36 and after the intervention was 85?7.61 with p= 0.000.Conclusion: It can be concluded that there is a possitive effect between giving prolanis module based on caring theory with systolic and diastolic blood pressure